بیسویں صدی میں علم حدیث کی تدوین وتحقیق ، منتخب مناہج کا تحقیقی وتقابلی جائزہ: In the 20th century, compilation and researching hadith, research and comparative review of selected methodology - Sohail Rashid; Dr. Hafiz Abdul Basit Khan (International Research Journal of Arabic and Islamic Studies, 2024)
The 20th century witnessed significant advancements in the compilation and research of Hadith. This era saw notable progress in the collection, organization, and publication of Hadith, fueled by technological and scholarly developments. Shaikh Shuaib Ar’naoot,Allama Nasir ul Deen Albani, Allama Ahmad Shakir and Zia ur Rahman Azmi's research seminaries hold an important place in Islamic academic history. Because they devoted their lives to preserving the intellectual capital of hadiths and conveying it to the ummah in its true form. There are some similarities and some differences in the research of these four scholars. Shaikh Shuaib Ar’naoot adopted modernity in the research of hadiths and researched deeply on both the Isnaad and the Matn of hadiths. Allama Ahmad Shakir's minhaj was based on traditional principles, but he examined hadiths keeping in mind the requirements of modern times. The important aspect of his services was that he combined modern scholarly principles while maintaining ancient principles. Allama Nasir ul Deen Al-Albaani's research was based on a classification of hadiths and he took an unusually cautious approach to raise the standard of health (Seht) of hadiths. He emphasized that only those hadiths that meet the standards of health should be accepted. Zia ur Rahman Azmi tried to clarify the health of hadiths as well as their meanings. Which led them to emerge as a balanced and robust research method.